Blind symbol timing recovery in the presence of IQ mismatch and DC offset - Gappmair, Wilfried; Koudelka, Otto (2014 9th International Symposium on Communication Systems, Networks & Digital Sign (CSNDSP), 2014)
Recovery of the symbol timing is of paramount importance in digital receivers. In this context, carrier-blind and non-data-aided algorithms are of particular interest, with Oerder-Meyr and Gardner algorithms as most prominent examples. On the other hand, it is to admit that direct-conversion receivers represent a most attractive solution for modern communication systems, which is mainly due to their small package size and the reduced power consumption. Scanning the open literature, it turned out quickly that waveform-related topics, like pulse shaping and symbol timing recovery, have not been addressed so far with regard to direct-conversion receivers. Motivated by this background, this particular issue is investigated in the current paper. The focus is on the estimator and detector characteristic of Oerder-Meyr and Gardner algorithms, but also on the jitter variance as the major figures of merit in this respect.